Inventarisasi Jenis Tumbuhan Obat dan Pemanfaatannya oleh Masyarakat di Desa Malintang Kecamatan Bukit Malintang Kabupaten Mandailing Natal Sumatera Utara - Salamat Ridoan; Ferdinand Susilo; Jamilah Nasution (Universitas Medan Area, 2022)
Medicinal plants are plants that have been identified and are known based on human observations to have bioactive compounds that have medicinal properties. This study aims to identify and describe the types of medicinal plants and their use by the community in Malintang Village, Bukit Malintang District, Mandailing Natal Regency, North Sumatra. Based on the research results obtained from interviews with the community totaling 17 people from 370 heads of families, it can be concluded that there are 30 types of plants from 20 families that are useful as medicine in Malintang Village, Bukuit Malintang District, Mandailing Natal Regency, North Sumatra Province. There are 16 types of plants that are used for leaf parts, 6 types of fruit parts, 5 types of rhizome parts, 4 types of flower parts, 3 types of seeds, 2 types of tubers, 1 part of the skin and roots of each plant.